2021
DOI: 10.21203/rs.3.rs-225462/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Precise detection of the germinomatous component of intracranial germ cell tumors of the basal ganglia and thalamus using placental alkaline phosphatase in cerebrospinal fluid

Abstract: Purpose: The disadvantages of biopsy for lesions in the basal ganglia and thalamus include a risk of various complications, difficulty in selecting the target tissue in some cases due to indistinct neuroimaging findings and limited availability of sample tissue. Placental alkaline phosphatase (PLAP) plays a decisive role in the diagnosis and management of intracranial germ cell tumors (IGCTs) in the basal ganglia and thalamus. The present study aimed to demonstrate the ability, specificity, and optimal use of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In the past 10 years, research on the regulative effects of aloin on bone formation and metabolic processes has achieved variable results. Alkaline phosphatase (ALP) is a marker of early osteoblast differentiation (Chiba, Aihara, & Kawamata, 2021). Pengjam et al (2016a) observed that 0.05 μM aloin treatment can significantly increase the ALP activity of MC3T3‐E1 cells, and cells treated with aloin for 2 weeks revealed significant calcium deposition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past 10 years, research on the regulative effects of aloin on bone formation and metabolic processes has achieved variable results. Alkaline phosphatase (ALP) is a marker of early osteoblast differentiation (Chiba, Aihara, & Kawamata, 2021). Pengjam et al (2016a) observed that 0.05 μM aloin treatment can significantly increase the ALP activity of MC3T3‐E1 cells, and cells treated with aloin for 2 weeks revealed significant calcium deposition.…”
Section: Resultsmentioning
confidence: 99%
“…Alkaline phosphatase (ALP) is a marker of early osteoblast differentiation (Chiba, Aihara, & Kawamata, 2021). Pengjam et al (2016a) observed that 0.05 μM aloin treatment can significantly increase the multinuclear cells, reduced the levels of cathepsin K expressed by osteoclast-specific genes, and inhibited both the activation of the NF-κB pathway induced by nuclear factor kappa-Β ligand and differentiation of RAW264.7 cells into osteoclasts.…”
Section: Osteogenesismentioning
confidence: 99%